With Voice and Pen: Coming to Know Medieval Song and How it was Made - Treitler, Leo 1931- (Oxford Oxford University, 2003)
Leo Treitler's seventeen classic essays trace the creation and spread of song (cantus), sacred and secular, through oral tradition and writing, in the European Middle Ages. The author examines songs in particular - their design, their qualities and character, their expressive meanings, and their adaptation to their communal and ritual roles - and explores the chances for, and the obstacles to, our understanding of traditions that were alive a thousand years ago. Ranging from c. 900 (when the written transmission of medieval songs began) to 1200, Treitler shows how the earlier, purely oral traditions can be examined only through the lens of what has been captured in writing, and focuses on the invention and uses of writing systems for representing these oral traditions. Each of these seminally influential essays has been revised to take account of recent developments, and is prefaced with a new introduction to highlight the historical issues.
Keywords: Music history; Plainchant